IMPROVING READING COMPREHENSION OF NARRATIVE TEXT THROUGH COMIC BOOK AT TENTH GRADE OF MAS RAUDHATUL AKMAL 2020/2021 ACADEMIC YEAR - Rahmah, Fitria Ainur (Faculty of Tarbiyah nad Teacher Training, 2021)
This study was aimed to find out the improvement of students’ ability in reading comprehension of Narrative text through Comic book in grade X MAS Raudhatul Akmal. The subject of this study was grade X MAS Raudhatul Akmal. It was consisted of 20 students. This research applied by Class Room Action Research. The technique of analysing data of this research was applied by using descriptive technique. The qualitative data was taken from diary notes, interview and observation sheet. The quantitative data was taken from the test. The result of the analysis showed that mean of the pre-test was 68,5, the mean of cycle I was 76 and the mean of cycle II was 82,5. The percentage of the students who got point up 75 also grew up, in the pre-test, the student who got point up 75 were only 2 of 20 students (8%). In the post-test I of cycle I, the students who got up 75 there were 11 of 20 students (55%). In the post test II, students who got up 75 there were 17 of 20 students (85%). The improvement of the Pre-Test to the Post-Test of cycle I was 77% and the improvement of Pre-test of cycle I to the post-test of cycle II was about 30%. From the data it indicate that the implementation of comic book was effective and from the data above it could be concluded that the students ability reading comprehension have been developed by using comic book. It’s related to the result of observation showed that the students were more interested and motivated in joining the class and they were enthusiastic during teaching learning process. They asked what they didn’t know, they gave response. The students were active, and they seemed enjoy discussion during teaching process.Keywords: Reading Comprehension, action research, Narrative Text, Comic Book